Review: Physical, physical chemistries, chemical and sensorial characteristics of the several fruits and vegetable chips produced by low-temperature of vacuum frying machine - AHMAD DWI SETYAWAN; SUGIYARTO SUGIYARTO; SOLICHATUN SOLICHATUN; ARI SUSILOWATI (Nusantara Bioscience, 2013)
Abstract. Setyawan AD, Sugiyarto, Solichatun, Susilowati A. 2013. Review: Physical, physical chemistries, chemical and sensorial characteristics of the several fruits and vegetable chips by produced low-temperature of vacuum frying machine. Nusantara Bioscience 5: 86-103. Frying process is one of the oldest cooking methods and most widely practiced in the world. Frying process is considered as a dry cooking method because it does not involve water. In the frying process, oil conduction occurred at high temperature presses water out of food in the form of bubbles. Fried foods last longer due to reduced water contents leading to less decomposition by microbes, even fried foods can enhance nutritional value and beautify appearance. Food frying technology can extend the shelf life of fruits and vegetables, while the frying oil is used to enhance the flavor of the products, but the use of improper frying oil can have harmful effects on human health. Vacuum frying is a promising technology and may become an option for the production of snacks such as fruit and vegetable crisps that present the desired quality and respond to the new health trends. This technique of frying food at a low temperature and pressure makes the nutritional quality of the food is maintained and the quality of the used oil is not quickly declined to become saturated oils that are harmful to human health. This technique produces chips that have physical, physicochemical, chemical, and sensorial properties generally better than chips produced by conventional deep-fat frying methods.